Preliminary study of ratio of amylose and amylopectin as indicators of glycemic index and in vitro enzymatic hydrolysis of rice and wheat starches - Murugadass, Gowri; Dipnaik, Kavita (International Journal of Research in Medical Sciences, 2018)
Background: Wheat and rice form the staple food of large majority of the population throughout the world. Starch is a carbohydrate which is a homopolymer consisting of a large number of D-glucose units joined by α- glycosidic bonds. Starch can be separated into two fractions-amylose and amylopectin. Amylose, Amylopectin ratio is an indicator of Glycemic Index. Starches with lower amylose content will have higher glycemic indexes. Invitro digestion of starch provides efficient means of analysing carbohydrate digestibility and hence glycemic properties of foods. Invitro digestion indicates how a given food item is likely to behave in vivo, in terms of rate and extent of sugar release from starch, by stimulating physiological processes occurring in the mouth, stomach and small intestine. The rate of starch hydrolysis which gives rise to sustained release of reducing sugars would be preferred by the diabetics. Methods: In our study, starches of wheat and rice were first isolated. Amylose and Amylopectin ratio was determined to predict the glycemic index of both. Wheat and rice having the same amylose and amylopectin ratio were selected for our study. These isolated starches were subjected to invitro enzymatic hydrolysis by salivary and pancreatic amylases. Reducing sugars released after hydrolysis and incubation of 0, 5, 10, 15, 20 and 30 minutes were estimated by Folin-Wu method. Statistical analysis was carried out in the form of unpaired student’s t-test to find significant difference between means of reducing sugars release by wheat and rice during enzymatic hydrolysis. Results: Having compared the starches of wheat and rice having the same amylose-amylopectin ratio, it was seen that the rice had low digestibility than the wheat starch. Rice starch releases less amount reducing sugars gradually while the wheat starch releases more reducing sugars rapidly in a short period of time. This can be due to amylopectin A which might be present in larger quantities in wheat starch than in rice starch which assists in rapid digestion of wheat starch. Conclusions: Our findings revealed that rice starch released less reducing sugars gradually over a period of time while wheat starch released more reducing sugars rapidly. So, rice is the best option for diabetics for consumption because of its comparatively low release of reducing sugars as compared to wheat.